2009
DOI: 10.1037/a0013954
|View full text |Cite
|
Sign up to set email alerts
|

Keyes's model of mental health with personal growth initiative as a parsimonious predictor.

Abstract: This research addressed issues at the heart of counseling psychology: operationalizing mental health and identifying parsimonious ways of predicting levels of mental health. The primary purpose of the study was to investigate the replicability of the structure of C. L. M. Keyes's (2002) model of mental health in 2 samples of college students (total N ϭ 244 women and 223 men). Results of confirmatory factor analyses supported this 3-factor model of psychological, social, and emotional well-being, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(236 citation statements)
references
References 39 publications
3
200
0
15
Order By: Relevance
“…Personal growth initiative is defined as ''intentional involvement in changing and developing as a person'' (Robitschek and Keyes 2009, p. 322); that is, a person's intentional involvement in the process of personal growth. Personal growth initiative has been found to be a strong predictor of various aspects of well-being, including life satisfaction Robitschek and Keyes 2009).…”
Section: Predictive Validitymentioning
confidence: 99%
“…Personal growth initiative is defined as ''intentional involvement in changing and developing as a person'' (Robitschek and Keyes 2009, p. 322); that is, a person's intentional involvement in the process of personal growth. Personal growth initiative has been found to be a strong predictor of various aspects of well-being, including life satisfaction Robitschek and Keyes 2009).…”
Section: Predictive Validitymentioning
confidence: 99%
“…In the previous research, College students' mental health was mostly measured by negative mental health scale, such as SCL-90 [12]. However previous studies on the connotative structure of mental health showed that the mental health includes positive and negative two important aspects, not only is the absence of mental illness, or the high-level subject well-being, but also is a complete state by combining the two, namely compete mental health [13]- [15]. From this perspective, the present study proposes to explore the relationship between psychological suzhi and the mental health indicators of positive and negative, and to investigate the influence of the factors on psychological suzhi to mental health, screen some factors which have greater influence on mental health, provide the basis for enhancing the pertinence of mental health education.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the findings of Robitschek and Keyes (2009) revealed that college students who are engaging in more intentional self-improvement (i.e., have relatively high levels of PGI), in comparison with their low-PGI peers, accept themselves more, have better relationships with others, see more purpose in life, perceive more control and mastery over their environment, and have a greater sense of autonomy or self-direction regarding their lives and daily choices. PGI has been defined as the degree to which individuals perceive themselves as being actively engaged in the change and growth process (Robitschek, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, they have a greater feeling of connection to their community, more understanding of the social world around them, a greater sense of contributing to their communities, a forward-looking perspective on society, and a generally favourable view of the people in their world. They also report feeling happier, having greater life satisfaction, and overall, having more positive feelings (Robitschek & Keyes, 2009). …”
Section: Introductionmentioning
confidence: 99%